Embodied Movement as Method: Attuning to Affect as Feminist Experimentation. (August 2021) - Fullagar, Simone; Pavlidis, Adele; Hickey-Moody, Anna; Coffey, Julia
Abstract : This article explores qualitative research methods that employ materiality and movement, images and body mapping to access research participant knowledges. We examine a methodologies workshop that we co-facilitated for academics and postgraduates. We position the workshop as a research assemblage, through which we facilitated four different methodological 'moves', to borrow from Barad's (2007) notion of 'cuts', to invite learning-knowing through the movement of affect. These embodied methodologies included: moving-writing sport, digital photovoice, movement improvisation, and body mapping somatic movement. Workshop participants were invited to experiment with each method as a means of engaging with tacit, or difficult to articulate knowledges. By exploring what these embodied 'moves' do to our ways of knowing, we traced the affective relations that entangle human and nonhuman worlds, self and others, researcher and researched through the workshop intra-actions. Our accounts of each method are diffracted through affective relations as we attune to bodies, vulnerabilities, openings, objects, texts, thoughts, surfaces, and senses, as means of (un)learning together. We articulate the kinds of productive (un)learning that moved us in different ways, and how embodied, feminist new materialist approaches might contribute to defamiliarised approaches to research.